Factors Influencing Patients' Decisions to use Health Services for Re-Treatment at Griya Medika Dompet Dhuafa Hospital Lampung - Ni Made Putri Afriasih; Nuraini Nuraini; Ramadhani Syafitri Nasution (PROMOTOR, 2024)
This study aims to identify factors that influence patients' decisions to reuse health services at the Griya Medika Dompet Dhuafa Lampung Hospital. The research method used was an analytical survey with a cross-sectional design. Data was collected through questionnaires, medical records, and valid references. The research results show that factors such as the quality of doctor/nurse service, facilities, speed of service, and distance have a significant influence on patient decisions. Facilities are the most dominant variable in influencing a patient's decision to return for treatment. Managerial implications and suggestions are presented to improve the quality of care and improve certain aspects that influence patient decisions.